ANALISIS KOMPARATIF RPP IPS PADA KURIKULUM 2013 DAN RPP SEDERHANA DALAM MENDUKUNG PEMBELAJARAN EFEKTIF DI SEKOLAH DASAR - Wildatul Umah; Muhammad Ma’dinul In’am Al Kamil; Erma Fatmawati; Mu'alimin (JCI Publisher, 2026)
Lesson Plan (RPP) is an important component in the learning process that functions as a guide for teachers in conducting teaching and learning activities. This study aims to analyze Social Studies (IPS) lesson plans in the 2013 Curriculum and the simplified lesson plans, as well as to examine the differences, strengths, and weaknesses of both in supporting the learning process. This research employs a descriptive qualitative approach using a library research method and comparative analysis. Data were obtained from official documents, books, and relevant scientific journals. The results show that the 2013 Curriculum lesson plan has complete, detailed, and systematic components, providing structured guidance for teaching, but it tends to be complex and burdens teachers administratively. Meanwhile, the simplified lesson plan only consists of three main components, namely learning objectives, learning activities, and assessment, making it more flexible, practical, and efficient. In Social Studies learning, the simplified lesson plan is considered more relevant as it accommodates contextual and student-centered learning. However, the effectiveness of the simplified lesson plan highly depends on teachers’ pedagogical competence in designing and implementing learning activities. Therefore, teachers’ skills and creativity are required to ensure that the simplified lesson plan can optimally achieve learning objectives.